Antidepressant-Like Actions of Inhibitors of Poly(ADP-Ribose) Polymerase in Rodent Models - Ordway, Gregory A (Int J Neuropsychopharmacol, 2017)
BACKGROUND: Many patients suffering from depressive disorders are refractory to treatment with currently available antidepressant medications, while many more exhibit only a partial response. These factors drive research to discover new pharmacological approaches to treat depression. Numerous studies demonstrate evidence of inflammation and elevated oxidative stress in major depression. Recently, major depression has been shown to be associated with elevated levels of DNA oxidation in brain cells, accompanied by increased gene expression of the nuclear base excision repair enzyme, poly(ADP-ribose) polymerase-1. Given these findings and evidence that drugs that inhibit poly(ADP-ribose) polymerase-1 activity have antiinflammatory and neuroprotective properties, the present study was undertaken to examine the potential antidepressant properties of poly(ADP-ribose) polymerase inhibitors. METHODS: Two rodent models, the Porsolt swim test and repeated exposure to psychological stressors, were used to test the poly(ADP-ribose) polymerase inhibitor, 3-aminobenzamide, for potential antidepressant activity. Another poly(ADP-ribose) polymerase inhibitor, 5-aminoisoquinolinone, was also tested. RESULTS: Poly(ADP-ribose) polymerase inhibitors produced antidepressant-like effects in the Porsolt swim test, decreasing immobility time, and increasing latency to immobility, similar to the effects of fluoxetine. In addition, 3-aminobenzamide treatment increased sucrose preference and social interaction times relative to vehicle-treated control rats following repeated exposure to combined social defeat and unpredictable stress, mediating effects similar to fluoxetine treatment. CONCLUSIONS: The poly(ADP-ribose) polymerase inhibitors 3-aminobenzamide and 5-aminoisoquinolinone exhibit antidepressant-like activity in 2 rodent stress models and uncover poly(ADP-ribose) polymerase as a unique molecular target for the potential development of a novel class of antidepressants.